1999
DOI: 10.1007/s002679900173
|View full text |Cite
|
Sign up to set email alerts
|

Use of Landsat Thematic Mapper Data to Assess Seasonal Rangeland Changes in the Southeast Kalahari, Botswana

Abstract: / Management problems arise in semiarid rangeland that are characterized by marked wet and dry seasons because of forage deficiencies in the dry season. These natural vegetation rangelands can sustain livestock all year long when forage and senesced grass are available into the dry season. Seasonal range condition data are required to provide a basis for pasture management to help locate dry season cover and thereby minimize overstocking and degradation. The generation of seasonal data using Thematic Mapper (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…Ben-Shahar 1998;Frost et al 1985;Parker & Witkowski 1999;Ringrose & Matheson 1991;Skarpe 1991;Tothill & Mott 1985;Verlinden 1998 andreferences in Huntley &Walker 1982;Walker 1985;White 2000). Remote sensing techniques are commonly used for regional studies (Palmer & van Rooyen 1998;Ringrose et al 1999aRingrose et al , 2000.…”
Section: Patterns Of Vegetation Structure Within the Kalahari Sand Sheetmentioning
confidence: 99%
“…Ben-Shahar 1998;Frost et al 1985;Parker & Witkowski 1999;Ringrose & Matheson 1991;Skarpe 1991;Tothill & Mott 1985;Verlinden 1998 andreferences in Huntley &Walker 1982;Walker 1985;White 2000). Remote sensing techniques are commonly used for regional studies (Palmer & van Rooyen 1998;Ringrose et al 1999aRingrose et al , 2000.…”
Section: Patterns Of Vegetation Structure Within the Kalahari Sand Sheetmentioning
confidence: 99%
“…Scientific techniques such as satellite remote sensing (e.g. Ringrose et al, 1999), ecological assessment (e.g. Perkins and Thomas, 1993), the measurement of soil properties (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Vegetative responses, including the southward migration of the main vegetation belts have been predicted using the BIOME model (Leemans in Hulme, 1996;Chipanshi & Ringrose, 2001). Global change studies in Botswana have indicated that most measurable change in the south-central Kalahari occurs in the form of localized bush encroachment (Ringrose et al, 1996(Ringrose et al, , 1999a, most likely in response to human induced disturbances (cf. Campbell & Stafford Smith, 2000) although regional change is also apparent (Vanderpost et al, 1998;Skarpe, 1990).…”
Section: Introductionmentioning
confidence: 99%